Zika Virus Infects Human Cortical Neural Progenitors and Attenuates Their Growth - Tang, Hengli; Hammack, Christy; Ogden, Sarah C.; Wen, Zhexing; Qian, Xuyu; Li, Yujing; Yao, Bing; Shin, Jaehoon; Zhang, Feiran; Lee, Emily M.; Christian, Kimberly M.; Didier, Ruth A.; et al. (Cell stem cell, 2016)
The suspected link between infection by Zika virus (ZIKV), a re-emerging flavivirus, and microcephaly is an urgent global health concern. The direct target cells of ZIKV in the developing human fetus are not clear. Here we show that a strain of the ZIKV, MR766, serially passaged in monkey and mosquito cells efficiently infects human neural progenitor cells (hNPCs) derived from induced pluripotent stem cells. Infected hNPCs further release infectious ZIKV particles. Importantly, ZIKV infection increases cell death and dysregulates cell-cycle progression, resulting in attenuated hNPC growth. Global gene expression analysis of infected hNPCs reveals transcriptional dysregulation, notably of cell-cycle-related pathways. Our results identify hNPCs as a direct ZIKV target. In addition, we establish a tractable experimental model system to investigate the impact and mechanism of ZIKV on human brain development and provide a platform to screen therapeutic compounds. [Display omitted] •Zika virus (ZIKV) infects human embryonic cortical neural progenitor cells (hNPCs)•ZIKV-infected hNPCs produce infectious ZIKV particles•ZIKV infection leads to increased cell death of hNPCs•ZIKV infection dysregulates cell cycle and transcription in hNPCs The suspected link between ZIKV infection and microcephaly is an urgent global health concern. Tang et al. report that ZIKV virus directly infects human cortical neural progenitor cells with high efficiency, resulting in stunted growth of this cell population and transcriptional dysregulation.